2007
DOI: 10.1007/s00423-007-0218-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and immunohistochemical characterization of isolated tumor cells by p53 status in gastrointestinal tumors

Abstract: ITCs detected by the antiepithelial antibody Ber-EP4 are present in a substantial proportion of apparently tumor-free lymph nodes. These cells impair patients' prognoses, irrespective of the underlying cell morphology. As approximately one third of Ber-EP4-positive cells in p53-positive primary tumors do not overexpress p53; their true tumorigenic origin needs to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…One recent study [31] characterized ITC in gastrointestinal tumors by p53. As one third of the ITC in p53-positive primary tumors did not overexpress p53, they concluded that their true tumorigenic origin needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study [31] characterized ITC in gastrointestinal tumors by p53. As one third of the ITC in p53-positive primary tumors did not overexpress p53, they concluded that their true tumorigenic origin needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Ber-EP4 is a 40 kDa transmembrane cell surface glycoprotein highly expressed in epithelial cancers and usually stains cytoplasmic with membranous accentuation 21 . Ber-EP4 is an established marker for immunocytochemical detection of tumor cells, 22,23,24 and detecting lymph node micrometastasis in gastric cancer 25,26 . High Ber-EP4 expression associates with the proliferation and progression of gastric cancer, especially in the diffuse type 27 .…”
Section: Methodsmentioning
confidence: 99%
“…21 Ber-EP4 is an established marker for immunocytochemical detection of tumor cells, 22,23,24 and detecting lymph node micrometastasis in gastric cancer. 25,26 High Ber-EP4 expression associates with the proliferation and progression of gastric cancer, especially in the diffuse type. 27 As most gastric cancer samples in this cohort are diffuse type, the choice of immunohistochemical marker was further supported.…”
Section: Choice Of Antibodies For Ihcmentioning
confidence: 99%